2012
DOI: 10.1007/s12070-011-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

Modified Radical Mastoidectomy: A Relook at the Surgical Pitfalls

Abstract: The primary aim of surgery for cholesteatoma is to eliminate the disease, to produce a safe and dry ear which is self cleansing, modify the anatomy of the tympanomastoid compartment so as to prevent recurrent disease and wherever possible to reconstruct the hearing mechanism. The advances in medical technology and the medical expertise gained over a period of time have greatly influenced the results in cholesteatoma surgery. The aim of the present study was to assess the intraoperative findings during revision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…We found that no excision of the head of the malleus intraoperatively was a major cause of residual lesions in the anterior epitympanic recess, consistent with the findings reported by Li et al [ 9 ] Prasanna Kumar et al described cholesteatoma at the sinodural angle (63%), and inadequate reduction of the posterior canal wall flush with the external auditory canal were the main concerns for recurrent or residual disease. [ 10 ] For the 19 ears (41.3%) exhibiting insufficient opening of the posterior tympanum, we removed the outer wall of the tympanic cavity and ground the facial neural crest low, which was useful in fully opening the posterior tympanum and forming a spacious surgical cavity with the external auditory canal and mastoid cavity to thoroughly remove lesions during surgery. Damage to the facial nerve should be avoided during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We found that no excision of the head of the malleus intraoperatively was a major cause of residual lesions in the anterior epitympanic recess, consistent with the findings reported by Li et al [ 9 ] Prasanna Kumar et al described cholesteatoma at the sinodural angle (63%), and inadequate reduction of the posterior canal wall flush with the external auditory canal were the main concerns for recurrent or residual disease. [ 10 ] For the 19 ears (41.3%) exhibiting insufficient opening of the posterior tympanum, we removed the outer wall of the tympanic cavity and ground the facial neural crest low, which was useful in fully opening the posterior tympanum and forming a spacious surgical cavity with the external auditory canal and mastoid cavity to thoroughly remove lesions during surgery. Damage to the facial nerve should be avoided during surgery.…”
Section: Discussionmentioning
confidence: 99%